From implementation to revising simulation integration into undergraduate physiotherapy training - A van der Merwe; R Y Barnes; M J Labuschagne (South African Medical Association, 2022)
Background. Careful consideration of an increasingly underprepared tertiary student population, the limited use of simulation in South African (SA) healthcare education and a changing healthcare education milieu is required from SA educators when implementing, evaluating and revising simulation integration. Objectives. To develop a conceptual framework for the integration of simulation in the SA undergraduate physiotherapy programme. Methods. A non-experimental descriptive research design was used. A purposive sample of 15 healthcare educationalists from SA and abroad were approached to participate in a modified Delphi survey, informed by the results obtained from a systematic review identifying simulation integration framework elements. Data were analysed as percentages, with feedback provided to panel members following each round. Results. Data saturation was achieved after round 3, with a response rate of 73.3% (n=11). The main findings suggested that student preparation prior to simulation-based learning experiences (SBLEs) should include orientation to SBLE logistics and expectations (73%), and could include informal assessment of theory (64%). Inclusion of the feedback/debriefing process (82%), methods (100%) and timing (85%) as part of student and educator preparation were also deemed essential. Panel members agreed that programme evaluation in line with stakeholder feedback (92%) is vital for guiding adjustments to the programme that is integrating simulation. Conclusion. The developed conceptual framework indicates the necessity of student and educator preparation to ensure optimal SBLE participation and outcome achievement. Programme sustainability should be ensured through programme evaluation and adjustment, in line with stakeholder feedback, best practice and accrediting professional body guidelines.